Increase in antibiotic resistance in diabetic foot infections among peruvian patients: a single-center cross-sectional study - Moya-Salazar, Jeel; Chamana, Jackelina M.; Porras-Rivera, Daniela; Goicochea-Palomino, Eliane A.; Salazar, Carmen R.; Contreras-Pulache, Hans (Frontiers in Endocrinology, 2023)
Background: Diabetic foot is one of the most significant complications in individuals with diabetes and is closely associated with lower limb amputation. The antibiotic susceptibility patterns of these bacterial isolates play a critical role in guiding effective treatment strategies We aimed to determine the most common bacterial agents causing diabetic foot infections in a tertiary-care hospital in Peru.Methods: Clinical and microbiological data were collected from 181 patients diagnosed with diabetic foot infections and positive microbiological culture results. All the samples were analyzed with the Vitek 2 compact system and the cut-off points were defined with the CLSI M100 guide. The data were segregated based on mono-microbial or poly-microbial cultures, bacterial types, and antibiotic susceptibility profiles.Results: A total of 32 bacterial species were identified, predominantly Gram-negative (63%). The most frequent bacterial agents isolated were Staphylococcus aureus (19.9%), Escherichia coli (12.2%), Pseudomonas aeruginosa (8.3%), and Proteus vulgaris (6.6%). These bacteria commonly exhibited resistance to Ampicillin, Ciprofloxacin, Levofloxacin, Trimethoprim-sulfamethoxazole, and Cefuroxime. E. coli showed the highest antibiotic resistance (19 antibiotics), while Gentamicin, Tobramycin, and Levofloxacin demonstrated the highest sensitivity against the most prevalent bacteria. Gram-negative bacteria also exhibited notable antibiotic-susceptibility to Meropenem, Piperacillin/tazobactam, and Amikacin. Regarding the presence of Extended-Spectrum Beta-Lactamase, 54 isolates tested positive, with 35 (64.8%) and 14 (42.4%) of these being S. aureus and E. coli. Conclusions: Bacterial agents causing diabetic foot infections pose a constant concern, particularly due to the increasing antibiotic resistance observed. This difficulty in treating the condition contributes to a higher risk of amputation and mortality. Further research on bacterial susceptibility is necessary to determine appropriate dosages for pharmacological treatment and to prevent the overuse of antibiotics.